1-Year Outcomes following Bioprosthetic Valve Fracture to Facilitate Valve-in-Valve Transcatheter Aortic Valve Replacement. Issue 3 (4th May 2021) - Chhatriwalla, Adnan K.; Allen, Keith B.; Saxon, John T.; Cohen, David J.; Nguyen, Tom C.; Loyalka, Pranav; Whisenant, Brian; Yakubov, Steven J.; Sanchez, Carlos; Sathananthan, Janarthanan; Stegman, Brian; Harvey, James; et al.
ABSTRACT: Background : Bioprosthetic valve fracture (BVF) improves the hemodynamic results of valve-in-valve transcatheter aortic valve replacement (VIV TAVR) by facilitating optimal expansion of the transcatheter heart valve (THV). Long-term outcomes following BVF are unknown. Methods : Consecutive cases of VIV TAVR and BVF (n = 139) performed at 11 sites were analyzed retrospectively. Hemodynamic measurements and aortic valve area (AVA) were assessed during the procedure and by echocardiography at 30-day and 1-year follow-up. Results : VIV TAVR and BVF resulted in significant improvements in mean valve gradient (42.3 ± 17.1 vs. 9.4 ± 5.8 mmHg, p < 0.001) and AVA (0.8 ± 0.4 vs. 1.8 ± 0.7 cm 2, p < 0.001) compared with baseline. Mortality was 2.3% at 30 days and 8.7% at 1-year. In adjusted models, mean valve gradient was higher (+5.1 [3.7, 6.5] mmHg, p < 0.001) and AVA was lower (−0.3 [−0.4, −0.2] cm 2, p < 0.001) at 1 month as compared to post-procedure. Between 30 days and 1 year, no significant changes in mean valve gradient (+1.4 [−0.5, 3.4] mmHg, p = 0.15) or AVA (−0.1 [−0.3, 0.03] cm 2, p = 0.11) were observed. In a multivariable analysis, use of a CoreValve (compared with a SAPIEN) THV was an independent predictor of a lower mean valve gradient at 1 year (−6.0 mmHg, p = 0.01). Conclusion : Survival is excellent following VIV TAVR and BVF and valve hemodynamics are stable between 30-day and 1-year follow-up. CoreValve use is a predictor of better hemodynamic results following VIV TAVR and BVF. Abbreviations: VIV TAVR: valve-in-valve transcatheter aortic valve replacement; THV: transcatheter heart valve; BSV: bioprosthetic surgical valve; PPM: patient prosthesis mismatch; BVF: bioprosthetic valve fracture; IQR: interquartile range; LVEF: left ventricular ejection fraction; AVA: aortic valve area; STS PROM: Society of Thoracic Surgeons predicted risk of mortality